Analisis Strategi Bersaing Merek Mie Instan Menggunakan Teknik Markov Chain Dan Game Theory (Studi Kasus Mie I Vs Mie S) - Ridwan, Muhammad; Sari, Rianita Puspa; Suseno, Agustian (TALENTA Publisher, 2021)
The Markov chain hypothesis is the hypothesis discussed in stochastic interactions, and has several applications. This strategy is always coordinated with future situations whose whereabouts cannot be known with certainty, so the community tries to carry out exercises with future directions full of vulnerabilities. Hypotheses are numerical ways of dealing with competitive planning situations and the struggles between different interests. This hypothesis is designed to examine the dynamic cycle of various serious states and includes at least two interests. In this situation, the information obtained from the voting results is then assessed for its legitimacy and quality by using the SPSS program. The consequence of counting with Markov chain's S Noodle items reduces the share of the entire industry by 5.8%, while the fun noodle items expands a portion of the entire industry by 41%, the side effect of the game hypothesis being specific. namely X1 with probability 0.5, X2 with probability 0.5 and X3 with probability 3.16. Meanwhile, to limit misfortune, Indomie consolidates three systems, namely Y1 with likelihood - 0.1, Y2 with likelihood 0.5 and Y3 with likelihood 1.